The association between frailty and perceived physical and mental fatigability: The Long Life Family Study. - Schumacher, Benjamin T.; Kehler, Dustin S.; Kulminski, Alexander M.; Qiao, Yujia; Andersen, Stacy L.; Gmelin, Theresa; Christensen, Kaare; Wojczynski, Mary K.; Theou, Olga; Rockwood, Kenneth; Newman, Anne B.; Glynn, Nancy W. (Journal of the American Geriatrics Society, 2024)
Background: Higher levels of frailty, quantified by a frailty index (FI), may be linked to fatigue severity as tasks become more physically and mentally demanding. Fatigue, a component of frailty research, has been ambiguous and inconsistent in its operationalization. Fatigability—the quantification of vulnerability to fatigue in relation to specific intensity and duration of activities—offers a more sensitive and standardized approach, though the association between frailty and fatigability has not been assessed. Methods: Using cross‐sectional data from the Long Life Family Study at Visit 2 (2014–2017; N = 2524; mean age ± standard deviation (SD) 71.4 ± 11.2 years; 55% women; 99% White), we examined associations between an 83‐item FI after excluding fatigue items (ratio of number of health problems reported (numerator) out of the total assessed (denominator); higher ratio = greater frailty) and perceived physical and mental fatigability using the Pittsburgh Fatigability Scale (PFS) (range 0–50; higher scores = greater fatigability). Results: Participants had mean ± standard deviation FI (0.08 ± 0.06; observed range: 0.0–0.43), PFS Physical (13.7 ± 9.6; 39.5% more severe, ≥15), and PFS Mental (7.9 ± 8.9; 22.8% more severe, ≥13). The prevalence of more severe physical and mental fatigability was higher across FI quartiles. In mixed effects models accounting for family structure, a clinically meaningful 3%‐higher FI was associated with 1.9 points higher PFS Physical score (95% confidence interval (CI) 1.7–2.1) and 1.7 points higher PFS Mental score (95% CI 1.5–1.9) after adjusting for covariates. Conclusions: Frailty was associated with perceived physical and mental fatigability severity. Understanding this association may support the development of interventions to mitigate the risks associated with greater frailty and perceived fatigability. Including measurements of perceived fatigability, in lieu of fatigue, in frailty indices has the potential to alleviate the inconsistencies and ambiguity surrounding the operationalization of fatigue and provide a more precise and sensitive measurement of frailty.